PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN DIMEDIASI LEARNING ORGANIZATION DI BPJS KETENAGAKERJAAN PUSAT JAKARTA - I Made Adnyana; Parhana Bahri (Universitas Nasional, 2020)
The Influence of Knowledge Management on Employee Performance in Mediation Learning Organizations at the Jakarta Central Employment BPJS.Human resources are very important in improving a company or organization. Where the resources in question are all employees in the company from the lowest level to the highest level incorporated in the work. Each employee can make a good or bad contribution to the company because the company's achievements or disasters depend on the performance of its employees. Therefore, management must always be developed to realize the importance of improving employee performance through Knowledge Management in Mediation. Learning organizations play an important role in improving the performance of their employees so that they are seen as affecting the company or organization. This paper aims to study the effect, Knowlegde Management on employee performance mediated by learning organizations to provide advice on how companies can improve the performance of their employees through effective programs where Knowledge Management has four variables. For independent variables: Tacit Knowledge (X1), Explicit knowledge (X2), Support leadership (X3), and Technology (X4). The dependent variable or Mediation is Learning Organization (Y1) and Performance (Y2). The research approach used for this study is in accordance with quantitative research, namely interviews, observations, and questionnaires. The model was analyzed using smartPLS 2.0 statistical software. This survey-based data was collected from 100 respondents. This study found that Tacit knowledge, Explicit Knowledge, Support Leadership and Technology had a positive and significant effect on employee performance mediated by Learning organizations.